PENGENALAN WAJAH MENGGUNAKAN BACKPROPAGATION NEURAL NETWORK DAN EKSTRAKSI CIRI INDEPENDENT COMPONENT ANALYSIS - Filipus Hanung Nugroho; Tony Tony; Agus Budi Dharmawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Face recognition is one way that can be used to identify a person. Recognize a person's face is an easy thing to do for humans. But face recognition is a difficult thing to do by intelligent machines, such as computers. The purpose of this application is to see the performance of the ICA method. The results of this experiment showed that the ICA method produces a higher success rate. ICA method produces a good success rate with a 78%-100% success rate. Key words Backpropagation Neural Network, Face Recognition, Independent Component Analysis